Implementasi SDGs Pada Anak Usia Sekolah Dasar Melalui BerLiMPah (Bersama Lima Menit Pungut Sampah) - Unggul, Latifa Destami; Rahim, Meiliza Erfa; Fazira, Nadia Kinanti; Sholihah, Nadiyatush; Rizkiana, Nila (Rengganis Jurnal Pengabdian Masyarakat, 2024)
This article discusses the implementation of SDGs in community service research, especially education on the grouping of waste types in State Elementary School 38 Mataram as a first step to increase students' awareness of the importance of sorting types of waste. Based on observations made, it was found that there has been no concrete action on grouping organic and inorganic waste in State Elementary School 38 Mataram. Therefore, students of the mathematics education study program at Mataram University who are registered as participants in the teaching campus of batch 6 placement of State Elementary School 38 Mataram initiated the "BerLiMPah" program. The purpose of this program is to provide knowledge related to sorting types of organic and inorganic waste, improve students' caring attitudes towards the environment, form a character cleanliness is part of faith, and familiarize students to always throw garbage in its place. The implementation method of the "BerLiMPah" program uses educational methods through the stages of preparation, socialization, and daily application. The result of the "BerLiMPah" program is that students know and understand the importance of sorting waste according to its type, the growth of positive habits to always maintain the cleanliness of the environment, especially the school environment, and the school environment becomes cleaner and convenient for the implementation of teaching and learning activities. It is hoped that this research can be continued and carried out more optimally in every community environment, not just in elementary schools, seeing that the objectives of research through this program are very important, one of which is as an effort to implement Indonesia's SDGs.